TRADISI BADANAN: Studi Living Hadits di Kecamatan Reteh, Indragiri Hilir - Maulana, Maulana; Masduki, Masduki (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study examines the Badanan tradition as a practice of silaturrahmi (maintaining social ties) among the Javanese diaspora in Parit 7 Pulai Kijang, Reteh District, Indragiri Hilir Regency, Riau. This tradition, which lasts from the first to the sixth day of Syawal, is a local manifestation of the hadiths of Prophet Muhammad SAW concerning the importance of maintaining familial and social relationships. Using a living hadith approach, this research aims to understand how the values embedded in the hadiths are realized in the social life of the community. Data was collected through field observations, in-depth interviews, and literature review. The findings indicate that the Badan tradition, once an essential instrument for preserving social harmony and Islamic values within the community, has declined in recent years due to changes in lifestyle, modernization, and a reduced participation of younger generations. This study recommends revitalizing the Badan tradition as a means of reawakening the values of hadith in the social practices of local Muslim communities.